An assessment of the comprehension of the preliminary 2007 version of the South African paediatric food-based dietary guidelines for Northern Sotho infants 6–12 months of age in Soshanguve and Ga-Rankuwa - Pretorius, Adeline (Stellenbosch : Stellenbosch University, 2015)
Thesis (MNutr--Stellenbosch University, 2015.